Design, Implementation and Performance Analysis of a Low-cost Optical Tachometer - Bakibillah, ASM; Uddin, Muhammad Athar; Haque, Shah Ahsanul (IIUC Studies, 2012)
Electrical and mechanical machineries are used in industrial and domestic applications. Measurement of speed of revolving machineries is necessary for their proper functioning and controlling. Tachometer is an instrument which is used to measure the speed of revolving shaft, gear and pulley. This paper describes the basic construction of a low cost optical tachometer and analyzes its performance. The basic tachometer circuit consists of two stages. In the first stage monostable wired around IC NE555 is used, and in the second stage a digital counter based 4-digit counter IC 74C926 is used for the construction of the tachometer. A 5V regulated power supply circuit and an infrared light source circuit are also used. The instrument can measure speed upto 9999 RPM. This speed measurement instrument performs well in terms of accuracy, and can be very useful due to its simplicity and low cost. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12263 IIUC Studies Vol.7 2011: 107-116